2019
DOI: 10.1155/2019/5683085
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Tablet Attachment in Teleophthalmology for Real-Time Video Transmission from Rural Vision Centers in a Three-Tier Eye Care Network in India: eyeSmart Cyclops

Abstract: Purpose. This study describes the development of an attachment for a smart tablet to stream live video information of an eye examination through the slit lamp. Methods. A tablet attachment was developed that enables the live streaming of video from the slit lamp from the rural vision centers of the LVPEI network. A video streaming solution like Skype Lite was used to transmit the same. The eyeSmart app was utilized for the documentation of the clinical information of the patients. Results. A tablet attachment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…The authors have already described their experience to use this modality in their multi-tier network for the rural vision centres consults through the development of the eyeSmart App to collect information[ 17 ], share clinical pictures for ophthalmologist opinion[ 18 ] and transmission of real time slit lamp video from their vision centres. [ 19 ] There is potential to explore the same for managing follow up patients coming from distant regions to the tertiary care centres through tele-ophthalmology and integrating this into the patient care services of the organization in near future. The possibility to integrate with elderly follow-up care for the geriatric patients presenting to our network supported by portable diagnostic equipment is being explored as well.…”
Section: Discussionmentioning
confidence: 99%
“…The authors have already described their experience to use this modality in their multi-tier network for the rural vision centres consults through the development of the eyeSmart App to collect information[ 17 ], share clinical pictures for ophthalmologist opinion[ 18 ] and transmission of real time slit lamp video from their vision centres. [ 19 ] There is potential to explore the same for managing follow up patients coming from distant regions to the tertiary care centres through tele-ophthalmology and integrating this into the patient care services of the organization in near future. The possibility to integrate with elderly follow-up care for the geriatric patients presenting to our network supported by portable diagnostic equipment is being explored as well.…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine is not new, having evolved well before the present pandemic in an attempt to address the medical care gap of various medical specialties in rural area. [ 6 7 8 9 ] Teleophthalmology and teleoptometry services provide an alternative approach in rural areas for the diagnosis of various diseases such as diabetic retinopathy, glaucoma, rehabilitative services for the visually impaired. [ 10 11 12 13 14 15 16 ] Telemedicine also saves money, time and travel for the patient.…”
mentioning
confidence: 99%
“…Kumar et al reported that the tele-ophthalmology services are cost-e ective for the patients in the rural areas in the substitute of conventional eye care at the higher centers [11]. Real time video transmission using tablet attachment in teleophthalmology has recently been described in literature [12]. Similar to these two studies, 73% of the patients in the rural centers could receive timely intervention in the current study with the help of eyeSmart EMR app in a tablet which had a verbal and video facility for face to face interaction of the patient and ophthalmologist occurred through the command center.…”
Section: Discussionmentioning
confidence: 99%